Dispersion of seeds of tree species by the leaf-cutting ant acromyrmex subterraneus molestans (hymenoptera: Formicidae) in viçosa, Minas Gerais State, Brazil - Pikart, Tiago Georg; Souza, Gabriely Köerich; Zanuncio, Teresinha Vinha; Zanetti, Ronald; Polanczyk, Ricardo Antonio [UNESP]; Serrão, José Eduardo; Zanuncio, José Cola (My University, 2010)
Leaf-cutting ants are the main pests in forest plantings, especially at the pre-cutting stage and immediately after the planting or in the beginning of sprouting. However, several genera of Formicidae are important seed disperses, including the leaf-cutting ants Atta and Acromyrmex. The present work aimed at studying the interaction between the leaf-cutting ant Acromyrmex subterraneus molestans Santschi, 1925 (Hymenoptera: Formicidae) and seeds of tree species in the campus of the Universidade Federal de Viçosa in Viçosa, Minas Gerais, Brazil. Seeds foraged by this ant were collected daily, in September 2009, and three behaviors of interaction were evaluated: removal of the attractive structure without transporting the seed (s), removal of the seed to another place (r) and attempt to remove the seed (t). Seeds of the tree species Copaifera langsdorfii Desf. (Leguminosae), Mabea fistulifera Mart. (Euphorbiaceae), Ricinus communis Linnaeus (Euphorbiaceae) and Senna macranthera (Collad.) Irwin et Barn. (Leguminosae) were foraged. Seeds of the first three present external attractive structures. All the seeds of S. macranthera were removed, while those of M. fistulifera were only partially removed. Acromyrmex subterraneus molestans presented interaction with the seeds of myrmecochorous and non-myrmecochorous species, demonstrating low selectivity during collecting activity. This is the first record of the leaf-cutting ant A. subterraneus molestans dispersing seeds of tree species in Brazil.
Keywords: Dispersion; Interaction; Leaf-cutting ants; Seeds